A Pioneer in Classics Education for Women: Abby Leach (1855-1918) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Abby Leach (1855-1918) was a seminal figure in American education. A pioneer in women’s higher education, she persuaded professors at Harvard to deliver their lectures to girls assembled in “The Annex” in Cambridge, Massachusetts. “The Annex” eventually became Radcliffe College. Leach went on to become a professor of Classics at Vassar, where she played a leading role in developing curriculum for women’s colleges at their formative stage, and she was the first woman president of the American Philological Association. The basic data about Abby Leach are presented in the Database of Classical Scholarship, a project of the Society for Classical Studies, housed at the University of South Carolina.
Keywords: Abby Leach; women’s education; Database of Classical Scholarship; Radcliffe; Harvard; Vassar; Greenough, J.B.; Eliot, Charles William; Goodwin, W.W.; Gildersleeve, B.L.; Macurdy, Grace